Addressing Mental Health Challenges: A Community Based Survey on Depression, OCD, Eating Disorders, and Psychosis Risk Among 18-44-year-olds in India - Sawant, Meenakshi; Waghachavare , Vivek Baliram; Kadam, Jitesh H; Gore, Alka D; Quraishi, Sanjay R (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Mental health is a complex issue with high prevalence but poor health facilities and health-seeking behaviour. The age group of 18-44 year-olds is socioeconomically crucial, however, their mental health is largely neglected. This research was conducted to study mental health problems among the 18–44-year-old age group. MATERIALS AND METHODS: This cross-sectional study was conducted among 1700 participants, aged 18-44 years old, from the urban and rural areas of Sangli district (Maharashtra state), India, using stratified random sampling. All ethical considerations were adhered to during data collection. Pre-validated tools namely, WHO-5 Well-Being Index, OCI-R, CAPE, etc., were used in data collection interviews. Statistical analysis was done using frequency (%) and the chi-squared test. RESULTS: The highest number of participants were positive for symptoms of obsessive-compulsive disorder (OCD) (n=336, 19.8%), followed by depression (n=326,19.2%), a high risk of psychosis (n=164, 9.6%) and an eating disorder (n=144, 8.5%). The area of residence (urban/rural) was associated with these mental illnesses. Depression was not significantly associated with any socio-demographic factors. OCD was significantly higher in participants from rural area, females, illiterates, and belonging to socioeconomic class III. Eating disorders were associated with rural areas, widowed status, and illiteracy. Psychosis risk was significantly higher in males, rural areas, joint families, and widower status. CONCLUSIONS: A very high proportion of 18-44-year-olds suffer or are at risk of various mental health conditions, requiring the development of targeted preventive and curative services. Rural areas should receive sufficient attention regarding mental health services.